Assessment of Hand-Washing Knowledge and Practice among Nursing Undergraduates in Saudi Arabia - Wajid Syed; Mahmood Basil A. Al-Rawi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Purpose. The present study investigated the knowledge and practice of hand hygiene among entry-level nursing students at King Saud University in Riyadh, Saudi Arabia. Participants and Methods: A cross-sectional, institutional-based study was conducted among Saudi nursing students over a period of four months at the King Saud University College of Nursing, using a structured, self-administered questionnaire that assessed demographics, knowledge, and the practice of hand washing. Results. A response rate of 95% was obtained. Of the 304 respondents, 66.1% (n = 201) were males. The majority of the students (94.2%) agreed that direct or indirect contact was the most important route for the transmission of healthcare-associated infection. In addition, most of the students washed their hands after contact with body secretions (89.5%), while 83.2% of them washed their hands before and after contact with patients. Furthermore, 83.6% of them applied soap water during hand washing, while 59.9% of the students used an alcohol-based hand rub for hand hygiene. Our results found that female students reported higher mean knowledge score of 10.09 ± 1.27, compared to male students 9.63 ± 1.48, indicating a significant association between the mean knowledge score of hand washing and gender (p=0.004). Similarly, the mean practice score was higher among female students (5.00 ± 1.25), in comparison to male students 4.62 ± 1.46, with a significant association between gender and mean practice score (p=0.037). Conclusion. The findings of this study revealed that Saudi nursing students exhibit adequate knowledge and practice of hand washing. However, the current findings revealed variation in the knowledge and practice scores with respect to gender. The present results could support students and health care professionals in improving their hygienic practice, which may help to provide the optimum therapeutic benefits to patients.